Jurnal Penyuluhan: Tingkat Difusi-Adopsi Inovasi Biogas di Kecamatan Lembang Kabupaten Bandung Barat - Nurul Dwi Novikarumsari, Siti Amanah, Basita Ginting Sugihen (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
This study aims to analyse the household characteristics of dairy farmer, perception of biogas innovation, access of information, the meeting with extension workers and factors affecting biogas diffusion and adoption in Lembang Sub District. Lembang Sub District has a potential of 4 149 dairy farmer households as prospected biogas adopters. Suntenjaya and Cibodas villages were selected as the research sites.